Forms of therapy of a child with selective mutism in the environment outside the family, embedded in a behavioral therapeutic approach - Kos, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The aim of this study is to present the forms of work and guidelines concerning the treatment of children with selective mutism in the light of the hypothesis that selective mutism should be perceived as an anxiety disorder that appears in childhood. On the basis of a thorough review of the literature, the Author discusses the forms of educational and therapeutic interaction that can be used in the treatment of children with selective mutism in accordance with the behavioural approach, and marginally with the psychodynamic approach.